Signifying Emotions: A Structural Analysis of Love in NIKI’S Nicole Album - Marshanda Chairunissa; Dedi Sulaeman; R. Myrna Nur Sakinah (PT. Global Research Collaboration, 2026)
Love is one of the most universal yet complex human emotions, often represented in song lyrics through symbolic and figurative language rather than direct statements. This study examines the representation of love in NIKI's Nicole album using Ferdinand de Saussure's semiotic theory, focusing on the relationship between signifier and signified in constructing emotional meaning. Using a descriptive qualitative design, this study analyzes the official lyrics of all twelve songs through documentation, close reading, and semiotic interpretation. The findings reveal that love is represented through interconnected emotional dimensions, including longing, heartbreak, emotional dependency, nostalgia, vulnerability, hope, acceptance, and healing. Rather than being expressed directly, these meanings are constructed through symbolic words, phrases, and recurring imagery whose signifieds develop across the album's narrative progression. The study concludes that Saussure's semiotic theory provides a systematic framework for explaining how linguistic signs construct emotional meaning and represent love as a dynamic emotional journey throughout the album.